Victims, civil society and transitional justice in Bosnia and Herzegovina - Humphrey Michael (Temida)
The role of victim organizations in the transitional justice process is examined in postwar Bosnia and Herzegovina (BiH). These organizations emerged in the context of the top-down accountability agenda driven by the international crisis intervention in the Balkan wars and the International Criminal Tribunal for the former Yugoslavia (ICTY). By contrast, in Latin America victim organizations emerged as a self-conscious movements of individuals galvanized by their traumatic experience of state repression and demanding accountability from the bottom-up. In BiH accountability became a condition for re-establishing state political and legal authority but also international financing for reconstruction and progress towards EU accession. Victim organizations were part of the NGO sector which grew rapidly in response to the neoliberal governance model of selforganizing civil society to transform post-socialist and postwar BiH. Non-governmental organizations (NGOs), run largely by professional middle class displaced from careers in the downsized state bureaucracy, became intermediaries between external donors and war affected populations. Victim organizations participated in the transitional justice process by supporting victims/witnesses in international and national prosecutions, tracing the missing persons and supporting the right of return of displaced populations. In BiH, victims’ organizations did not emerge as social movements advocating for citizenship and social justice, but became incorporated in the neoliberal governance model, sponsored by international agendas for stabilization, democratization and EU accession.